The Efficacy Comparison Between Guan-Fu Base A Hydrochloric Injection vs. Propafenone Hydrochloric Injection in the Treatment of Arrhythmia: Systemic Review and Meta-Analysis - Song, Jinming; Tang, Yao; Gao, Chao; Hou, Xiaofeng; Liu, Xinyue; Xu, Zongpei (Frontiers in Cardiovascular Medicine, 2021)
Objective： To determine using a systematic assessment and meta-analysis if GFA injection is an appropriate substitute of propafenone for arrhythmic. Design: Conduct a systematic review and meta-analysis of randomized controlled trials. Data source: PubMed, Web of Science, Cochrane Library, Embase, Wan-Fang Database, VIP, CNKI, Sino Med from their inception to 7 March 2020. Eligibility criteria for selecting studies: Inclusion of randomized controlled trials, which draws a comparison between GFA and propafenone. Evaluation of study integrity and conducted an extraction of independent data. Main outcome measure： Efficacy. For supraventricular tachycardia, it is considered effective if it is reversed within 40 min. (without considering Recurrence). For premature ventricular beats, if they are reduced by more than 50% within 6h. Results: Included in this current study are 1294 research subjects pooled from 14 clinical studies. From the pooled assessment, GFA is demonstrated to be the equivalent of propafenone regarding the potency of effectiveness for tachycardia (RR=1.11, 95%CI:0.96, 1.28, P=0.15). The subset analysis indicated that GFA has a better effect on premature ventricular beats (RR=1.35 95%CI:1.07, 1.70, P=0.01) and a similar effect on supraventricular tachycardia (RR=1.07 95%CI:0.98, 1.12, P=0.21). GFA effectiveness is lesser than propafenone in the case of mean converting time， (WMD=-1.18, 95%CI: -2.30, -0.07, P=0.04), systolic blood pressure (WMD = -3.53, 95% CI: -6.97, -0.09, P =0.04) and QRS complex (WMD = -3.82, 95% CI: -6.96, -0.69, P = 0.02). Both GFA and propafenone have identical effects for diastolic blood pressure, heart rate, P-R interval and QTc interval. Conclusion: A meta-analysis of RCTs was performed across 14 clinical trials, whereby 1294 patients are used as research subjects. From the results, it is revealed that the effect exhibited by GFA injection is similar to the propafenone injection when treating premature ventricular beats or supraventricular tachycardia. Nevertheless, in certain academic disciplines, it was found that GFA is safer and beneficial compared to Propafenone. Based on facts from relevant studies, GFA is deemed applicable during clinical practice.